Relasi Tokoh Agama dan Calon Kepala Desa dalam Pemilihan Kepala Desa Mulyorejo Kecamatan Silo Kabupaten Jember - Mohammad Amin Risqi Maulidi; Muhibbin Muhibbin (Icon: Islamic Communication and Contemporary Media Studies, 2022)
Pilkades a village head election activity which is considered closest democratic event to village community. Various elements of village community took part in  success of  democratic party, all groups took part in  village political contestation, such as success team to become village head candidates. The focus of the problems: 1) What are the reasons for the village head candidates to involve religious leaders in the 2021 village head election in Mulyorejo Village? 2) How to build communication between village head and religious leaders in 2021 Pilkades in Mulyorejo Village? 3) What is the impact of the involvement of religious leaders on village head candidates in the 2021 village head election in Mulyorejo Village? The objectives of study: 1) to describe  reasons for village head candidates to involve religious leaders in the Pilkades in Mulyorejo Village. 2) to describe how the candidate for village head builds communication with religious leaders. 3) to describe the impact of the involvement of religious leaders on village head candidates. The researcher descriptive qualitative approach. Data collection: interviews, documentation, observation. The data analysis: data collection, data reduction, data presentation,conclusion drawing. Research conclusions; 1) Broadly speaking, the reasons for the four candidates to involve religious leaders are varied, but of course to gather people's voices. 2) Relationships built by prospective village heads with religious leaders use massive and repeated approaches. 3) The impact  the involvement of religious leaders certainly reaps positive and negative impacts such as disappointment and satisfaction felt by the four candidates.